1999
DOI: 10.1046/j.1365-313x.1999.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrotransposon BARE‐1: expression of encoded proteins and formation of virus‐like particles in barley cells

Abstract: Summary Retrotransposons are ubiquitous and major components of plant genomes, and are characteristically retroviral‐like in their genomic structure and in the major proteins encoded. Nevertheless, few have been directly demonstrated to be transcribed or reverse transcribed. The BARE‐1 retrotransposon family of barley (Hordeum vulgare) is highly prevalent, actively transcribed, and contains well conserved functional regions. Insertion sites for BARE‐1 are highly polymorphic in the barley genome. Here we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 59 publications
2
44
0
Order By: Relevance
“…Dot blot data and combined restriction mapping and hybridization analyses of BAC (Bacterial Artificial Chromosome) clones indicated that, in barley and other Hordeum species, BARE-1 LTRs vastly outnumber (16 ‫ע‬ 2 ‫)ן‬ BARE-1 elements containing internal domains. (Jääskeläinen et al 1999;Vicient et al 1999). These data would be consistent with intraelement LTR recombination generating solo LTRs, at least of BARE-1.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Dot blot data and combined restriction mapping and hybridization analyses of BAC (Bacterial Artificial Chromosome) clones indicated that, in barley and other Hordeum species, BARE-1 LTRs vastly outnumber (16 ‫ע‬ 2 ‫)ן‬ BARE-1 elements containing internal domains. (Jääskeläinen et al 1999;Vicient et al 1999). These data would be consistent with intraelement LTR recombination generating solo LTRs, at least of BARE-1.…”
supporting
confidence: 82%
“…It is transcribed in somatic tissues (Suoniemi et al 1996) and is translated, processed, and assembled into virus-like particles (Jääskeläinen et al 1999). Dot blot data and combined restriction mapping and hybridization analyses of BAC (Bacterial Artificial Chromosome) clones indicated that, in barley and other Hordeum species, BARE-1 LTRs vastly outnumber (16 ‫ע‬ 2 ‫)ן‬ BARE-1 elements containing internal domains.…”
mentioning
confidence: 99%
“…Previous studies have shown that some of these retroelements are also transcribed in different Triticeae species (Pearce et al 1997;Suoniemi et al 1996b) though no quantification of their abundance is available. Translation products of Ty1-copia-type retrotransposons have been recently detected immunologically in barley (Jääskeläinen et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Reverse transcription follows transcription, and depends upon a (-)-strand initiation site (PBS), which is generally complementary to a tRNA in LTR retrotransposons, and a (+) strand initiation site (PPT), which is purinerich. These are highly conserved both for BARE-1 (82) and LARD elements (39) (36). Furthermore, BARE-1 GAG antibodies also detect a full-length translation product and its proteolytic processing products from barley and other cereals including rice (90).…”
Section: B Activation Of Retrotransposons By Stress Factorsmentioning
confidence: 99%
“…Translation of a third encoded domain, for the envelope protein, has not yet been directly shown in barley for the Bagy-2 element, although the requisite RNA splicing takes place (89). The GAG and integrase products of BARE-1 appear able to form virus-like particles, which can be visualized from sucrose gradients, associated with reverse transcriptase activity (36).…”
Section: B Activation Of Retrotransposons By Stress Factorsmentioning
confidence: 99%